The Role of Digital Transformation on the Performance of Public Elementary Schools in the Industrial Revolution 4.0 and Society 5.0 Era - Hariyasasti, Yayuk (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
This study aims to test the effect of digital transformation on the performance of elementary schools. Digital transformation and innovation are in the spotlight in the Industrial Revolution 4.0 and Society 5.0 eras that influence and change many things in the field of education. This study uses a quantitative approach. Data collection uses a survey through the distribution of questionnaires. The respondents of this study were 234 elementary school teachers. The hypothesis testing of this study uses Partial Least Square-Structural Equation Modeling (PLS-SEM) processed with SmartPLS. The results of the study show that digital transformation has a positive effect on school performance. The findings of this study prove that digital transformation has a positive effect on school performance which can encourage schools to continue to strive for their competitive advantage in providing educational services.